2014
DOI: 10.1128/jvi.03128-13
|View full text |Cite
|
Sign up to set email alerts
|

Developing High-Throughput HIV Incidence Assay with Pyrosequencing Platform

Abstract: Human immunodeficiency virus (HIV) incidence is an important measure for monitoring the epidemic and evaluating the efficacy of intervention and prevention trials. This study developed a high-throughput, single-measure incidence assay by implementing a pyrosequencing platform. We devised a signal-masking bioinformatics pipeline, which yielded a process error rate of 5.8 ؋ 10 ؊4 per base. The pipeline was then applied to analyze 18,434 envelope gene segments (HXB2 7212 to 7601) obtained from 12 incident and 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Accordingly, HIV has been classified into types, groups, subtypes or clades, circulating recombinant forms (CRF) and unique recombinant forms (URF) mainly based on the diversity of the viral env and pol genes [65–67]. Although to date most of the deep sequencing studies of HIV have focused on drug resistance and tropism, the methodology has been used to characterize novel HIV recombinants [69] and to determine HIV incidence [70]. Interestingly, deep sequencing has been particularly useful in the detection and characterization of HIV superinfection events, which seem to occur at higher rates than previously identified [71].…”
Section: Applications In General Virologymentioning
confidence: 99%
“…Accordingly, HIV has been classified into types, groups, subtypes or clades, circulating recombinant forms (CRF) and unique recombinant forms (URF) mainly based on the diversity of the viral env and pol genes [65–67]. Although to date most of the deep sequencing studies of HIV have focused on drug resistance and tropism, the methodology has been used to characterize novel HIV recombinants [69] and to determine HIV incidence [70]. Interestingly, deep sequencing has been particularly useful in the detection and characterization of HIV superinfection events, which seem to occur at higher rates than previously identified [71].…”
Section: Applications In General Virologymentioning
confidence: 99%
“…To date, most longitudinal investigations of HCV diversity have utilized population or clonal sequencing of samples from a limited number of individuals. Deep sequencing studies have demonstrated improved sensitivity for detection of minor sequence variants, compared to clonal sequencing, enabling highly sensitive, specific differentiation of acute and chronic HIV infections, but similar differentiation analyses have heretofore not been applied to HCV. In this study, amplicons from the HCV nonstructural 5B (NS5B) region from 77 individuals with documented seroconversion time frames were deep sequenced to assess its potential to differentiate acute from chronic infection.…”
mentioning
confidence: 99%
“…Unfortunately, samples from individuals infected with HIV-1 non-B subtypes (6,7), from elite controllers (8), from individuals treated with antiretroviral drugs (8,9), and from individuals with advanced stages of disease (7,9) can be misclassified on the basis of serological criteria because of delayed or reduced production of HIV-specific antibodies. Nonserological HIV-1 incidence assays (10,11) and algorithms combining serological and nonserological biomarkers have therefore been developed (12,13). HIV-1 diversity is considered to be a candidate nonserological biomarker, as it increases during the course of infection in antiretroviral treatment (ART)-naive individuals.…”
mentioning
confidence: 99%
“…HIV-1 diversity is considered to be a candidate nonserological biomarker, as it increases during the course of infection in antiretroviral treatment (ART)-naive individuals. Viral diversity can be determined by single-genome sequencing (11), next-generation sequencing (10), and high-resolution melting assays (12), but direct Sanger population sequencing can also reflect HIV-1 polymorphisms via ambiguous base calls (14)(15)(16).…”
mentioning
confidence: 99%